THE IMPACT OF PREGNANT WOMEN NUTRITIONAL STATUS HISTORY WITH STUNTING IN TODDLERS AGED 2-3 YEARS - Eva Silviana Rahmawati Rahmawati; Mariyatul Qiftiyah Qiftiyah (International Journal of Midwifery Research, 2021)
Stunting that take place in childhood will have an impact in the future, which can cause intelligence quotient (IQ) disorders, psychomotor development, motor skills, and neurosensory integration, having an average IQ of 11 points lower than children who do not Stunting. This research was to analyze The Impact Of Pregnant Women Nutritional Status History With Stunting In Children Aged 2-3 Years. The research design used was Case Control. This research was conducted in 5 posyandu, Tegalagung Village, Semanding District, Tuban Regency. This research was conducted in January-March 2021. This study using a total sampling technique, the sample of this study was some toddlers aged 2-3 years in Tegalagung Village, Semanding District, Tuban Regency who met the inclusion criteria. Data analysis used the Spearman test with a significant value of 0.05. Based on the results of SPSS version 21 using the Analysis using Spearman test got the result p-value = 0.635, because the p-value > 0.05 This shows that H1 is rejected, meaning that there is no significant impact between maternal nutritional status during pregnancy and the incidence of stunting in toddlers. 2-3 years old in Tegalagung Village, Semanding District, Tuban Regency. The results of this study are expected to be a source of information for health workers, especially midwives in providing midwifery care to mothers during pregnancy and toddlers to deal with stunting in toddlers